Peningkatan Prestasi Belajar PKN Melalui Metode ROLE PLAYING pada Siswa Kelas 5 Sekolah Dasar - Fitri Novita Sari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
: This study aims to improve student achievement in Civics Education (PKn) for fifth-grade elementary school students through the implementation of the Role-Playing method. The study was motivated by low student learning outcomes resulting from teacher-centered instruction, which led to a lack of student engagement in the learning process. A Classroom Action Research (CAR) design was employed, conducted over two cycles. The subjects of the study were 25 fifth-grade elementary school students. Data collection techniques included tests, observation, documentation, and field notes. Data analysis was conducted using both quantitative and qualitative descriptive methods. The results indicate that the Role-Playing method successfully improved student achievement. In the pre-cycle stage, the student mastery rate was 48% with an average score of 65.2. This increased to 72% with an average score of 74.8 in Cycle I, and further rose to 92% with an average score of 86.4 in Cycle II. Additionally, student activity and participation during lessons also improved. Thus, the Role-Playing method is effective for enhancing Civics Education achievement among fifth-grade elementary school students.